Vitreous Diagnosis in Neoplastic Diseases - Mónica Asencio-Duran; José Luis Vallejo-Garcia; Natalia Pastora-Salvador; Agustín Fonseca-Sandomingo; Mario R. Romano (Mediators of Inflammation)
Vitreous body is an intraocular structure, origin of diverse pathologies, but is also the place where cells and inflammatory mediators are released coming from several pathologic processes. These inflammatory reactions can happen in any other ocular location like choroid, retina, optic nerve, or ciliary body and vitreous humor constitutes a stagnant reservoir for these resulting substances and debris. Through the recent techniques of vitreous collecting, handling, and analysis, increasingly more sophisticated and with fewer complications, cellularity and molecules in the vitreous of challenging pathologies for the ophthalmologist can now be studied. The most usefulness for vitreous diagnosis would be the masquerade syndromes, and the best exponent in this group is the primary vitreoretinal lymphoma (PVRL), in which cytology and an IL-10/IL-6 ratio more than 1 is fundamental for the diagnosis.